2017
DOI: 10.1007/s00590-017-1998-5
|View full text |Cite
|
Sign up to set email alerts
|

Distraction osteogenesis reconstruction of large segmental bone defects after primary tumor resection: pitfalls and benefits

Abstract: Successful cure is achieved in almost 70% of patients with primary bone sarcomas with currently available therapies. Some soft tissue sarcomas require wide bone resection in order to achieve appropriate margins for cure of disease, and patients undergoing these procedures need durable reconstruction. Biological reconstruction has been shown to provide patients with superior long-term results over other alternatives. Distraction osteogenesis is well studied in the correction of deformities as well as in address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 63 publications
0
44
0
Order By: Relevance
“…However, two studies compared patients who underwent DO with and without chemotherapy and it did not demonstrate any difference in the bone healing process between patient groups [73,74]. The hypothesis proposed is that DO's effect on osteoblast may counteract the inhibitory effects of chemotherapy [75].…”
Section: Distraction Osteogenesis After Oncologic Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…However, two studies compared patients who underwent DO with and without chemotherapy and it did not demonstrate any difference in the bone healing process between patient groups [73,74]. The hypothesis proposed is that DO's effect on osteoblast may counteract the inhibitory effects of chemotherapy [75].…”
Section: Distraction Osteogenesis After Oncologic Surgerymentioning
confidence: 99%
“…Also, in a rabbit mandible model, it was found that osteogenesis is delayed after a 60-Gy dose of radiation, even though viable osteoblast and osteocytes may still be present [81]. It is therefore likely that distraction osteogenesis is negatively affected by radiation [75].…”
Section: Distraction Osteogenesis After Oncologic Surgerymentioning
confidence: 99%
“…The suggested advantages of this technique are: precise restoration of limb length discrepancies; stimulation effect on soft-tissue healing; easier management of potential infection; and durable biologic reconstruction with good long-term functional results. 3…”
Section: Segmental Bone Transportmentioning
confidence: 99%
“…The biological reconstruction implies that the diseased bone is replaced by an expendable, which completely replaces the role of the removed portion and can be classified as either viable or nonviable. The former involves vascularized bone graft and lengthening of the bone, [ 14 ] while the latter involves devitalized tumor bone [ 15 ] and allograft. Vascularized bone grafting has been reported as a safe and reliable procedure for reconstruction of segmental skeletal defects resulting from intercalary resection of malignant bone tumors.…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 , 17 ] Distraction osteogenesis with bone transport techniques for such significant bony defects involves a lengthy period in a cumbersome frame and a high incidence of complications, thus making it far from an ideal solution for these challenging cases. [ 14 ] Massive allografts are widely used because of biological fixation and attachments for soft tissue anchorage, with the problems of procurement, storage, immunological responses, and possible infection. Over recent years, there has been a great interest in recycling the tumor bone itself by various methods of sterilization and re-implantation.…”
Section: Introductionmentioning
confidence: 99%